Internet of Things in military applications - Sokolović, Vlada S.; Marković, Goran B. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The term Internet of Things (IoT) usually refers to the collective network of connected devices and the technology that facilitates communication between these devices and the cloud, as well as among these devices. The IoT concept is lately considered and applied as the appropriate in design of systems intended for distribution of data and information between heterogeneous devices with the aim to improve efficiency and effectiveness of business and decision making. The IoT enables energy and supply chain monitoring, production coordination, equipment performance optimization, transportation, public health, and improves workers' safety and health. In addition to smart devices, IoT technology also enables the connection of various sensors as a source of data on various physical phenomena, and, based on the information obtained, it is possible to control the operation of devices, make predictions, make decisions, etc. In this paper, specific areas of the application of the IoT in the defense and security sector are analyzed in order to identify the possibilities of applying modern technologies in raising the defense potential of the state and define the directions of future research in the subject area.Methods: The methods of content analysis of current research were applied, and then, with the deductive method, conclusions were reached about the future directions of the development of IoT technology.Results: A detailed analysis of past and ongoing research in the defense and security sector was carried out, and potential directions of future research into the IoT were given in order to increase the operational capabilities of armed forces.Conclusion: IoT services will certainly contribute to a greater degree of automation and improvement of the quality of military decisions on the battlefield, especially in the conditions of unexpected scenarios in an unpredictable hostile environment, thus facilitating the reduction in both human and material losses in operations.
Keywords: internet of things; defense and public safety; internet of things applications; localization and target detection; military logistics